Detection and characterization of single molecules in aqueous solution - Zander, C; Sauer, M; Drexhage, K; Ko, D; Schulz, A; Wolfrum, J; Brand, L; Eggeling, C; Seidel, C (1996)
Using a confocal microscope with a single-photon avalanche photodiode as detector, we studied photon bursts of single Rhodamine 6G (R6G) and Rhodamin B-zwitterion (RB) molecules in aqueous solution by excitation of the lowest excited singlet state S1 with a frequency-doubled titanium:sapphire laser. Multichannel scaler traces, the fluorescence autocorrelation function and fluorescence decay times determined by time-correlated single-photon counting have been measured simultaneously. The time-resolved fluorescence signals were analyzed with a maximum likelihood estimator. Fluorescence lifetime patterns in steps of 100 ps were generated by convolution with the excitation pulse. The lifetime of the S1 state was derived from the Kullback-Leibler minimum discrimination information. We are able to demonstrate for the first time identification of two different single dye molecules via their characteristic fluorescence lifetimes of 1.79 ± 0.33 ns (RB) and 3.79 ± 0.38 ns (R6G) in aqueous solution.